1987
DOI: 10.1136/adc.62.7.671
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of specific gravity and osmolality of urine in neonates and adults.

Abstract: SUMMARY There is good correlation between the specific gravity and osmolality of urine obtained from neonates and adults, if specimens contain neither protein nor glucose. The regression equations between specific gravity and osmolality, however, differ considerably between the two age groups, maturation to the adult regression occurring within the first 5 years of life. Specifically derived regression equations should therefore be used when predicting urine osmolality from measurement of specific gravity in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 5 publications
2
27
0
Order By: Relevance
“…Another study showed that UD was well correlated with mU osm but the wide dispersion made it “impossible to use UD as a dependable clinical estimate of U osm ” [46]. Moreover, UD or specific gravity cannot be used if urine contains proteins or glucose [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that UD was well correlated with mU osm but the wide dispersion made it “impossible to use UD as a dependable clinical estimate of U osm ” [46]. Moreover, UD or specific gravity cannot be used if urine contains proteins or glucose [47]. …”
Section: Discussionmentioning
confidence: 99%
“…While evaluating the correlation between the refractometer measured SG and the osmolality it was observed that at the same osmolality younger children had higher SG readings as compared to older children and adults (Fig. 5) [14,25]. A similar observation of a higher SG reading at the same osmolality was also made with the reagent strip method [13].…”
Section: Influence Of Patient Agementioning
confidence: 61%
“…Although the same changes are expected to cause lower refractometer SG readings, in reality refractometer SG readings in young children are higher due to high concentrations of free amino acids and low molecular weight proteins in their urine. This discrepant association between SG and osmolality shows a rapid progression towards the adult pattern during the first 2 years of life and is completed around 5 years of age [25]. It is, therefore, obvious that the equation used for estimating osmolality from the SG value in older children and adults is not valid for younger children.…”
Section: Influence Of Patient Agementioning
confidence: 96%
“…We emphasize that the formula is valuable regardless of the presence of HF. Urine SG has been known to correlate with U-OSM traditionally, 16 but it appears to be too crude to estimate U-OSM precisely, as shown in previous studies. 17, 18 In the present study, urine SG was not a good predictor of TLV response.…”
Section: Baseline Patient Characteristicsmentioning
confidence: 95%